2017
DOI: 10.1108/bpmj-10-2015-0146
|View full text |Cite
|
Sign up to set email alerts
|

The development of service provider’s BPO-IT framework

Abstract: Purpose The decision to operate BPO-IT organisational model by a business process outsourcing (BPO) service provider has far reaching benefits. The purpose of this paper is to develop a service provider’s BPO-IT framework that provides in-house IT function (software) required to process client services. Design/methodology/approach The multi-case study adopted an exploratory sequential mixed method research approach. In the first instance, seven BPO service provider organisations were investigated in the qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…However, Edvardsson et al (2020) defined business outsourcing as a procedure of transmitting several activities of an organization to another firm to provide a major advantage to the system. Most of the researchers believe that outsourcing is anything that happens or occurs outside of a firm, which improves trust and dependency between partners (Wibisono et al, 2019) According to Ikerionwu et al (2017), companies' successes depend on the business process and outsourcing service providers. However, outsourcing has a significant impact on business performance (Awe, 2018), has a substantial effect on increasing the firm's value (Prajapati et al, 2020), has a significant impact on the employer depiction ideal process (Sim et al, 2016).…”
Section: Business Outsourcingmentioning
confidence: 99%
“…However, Edvardsson et al (2020) defined business outsourcing as a procedure of transmitting several activities of an organization to another firm to provide a major advantage to the system. Most of the researchers believe that outsourcing is anything that happens or occurs outside of a firm, which improves trust and dependency between partners (Wibisono et al, 2019) According to Ikerionwu et al (2017), companies' successes depend on the business process and outsourcing service providers. However, outsourcing has a significant impact on business performance (Awe, 2018), has a substantial effect on increasing the firm's value (Prajapati et al, 2020), has a significant impact on the employer depiction ideal process (Sim et al, 2016).…”
Section: Business Outsourcingmentioning
confidence: 99%
“…In both instances, it is commonly a norm that outside vendors are regarded as specialist who can provide similar or better levels of service at a lower cost than available in-house. Notwithstanding the specific factors in the outsourcing decision framework, research has shown that the mode of service delivery is critical in determining a successful relationship [21]. Therefore, this section presents three key means of delivery mode available for BPOs: dedicated private network, cloud computing, and desktop virtualization.…”
Section: Background Of Studymentioning
confidence: 99%
“…Table 3 shows that the delivery mode is mutually agreed, but the provider's expertise plays a significant contribution to the decision making. In this aspect, large service provider organizations with many years of experience tend to influence the decision making [21]. The next section is the quantitative investigation of a larger number of service providers in India.…”
Section: Q5mentioning
confidence: 99%